Enhanced Efficiency of Perovskite Solar Cells by using Core–Ultrathin Shell Structure Ag@SiO2 Nanowires as Plasmonic Antennas. (16th October 2017) - Wang, Yang; Zhou, Xue; Liang, Chao; Li, Pengwei; Hu, Xiaotian; Cai, Qingbin; Zhang, Yiqiang; Li, Fengyu; Li, Mingzhu; Song, Yanlin
Abstract: The structural advantages and localized surface plasmon resonance (LSPR) effect of Ag@SiO2 nanowires when used as plasmonic antennas possess the features of fast electron transmission by 1D metal nanomaterials, high light harvesting, and electron–hole separation through the LSPR effect. By optimizing the concentration of Ag@SiO2 nanowires (0.06 wt%) in the active layer of a device, high power conversion efficiency of 18.03% and a negligible photocurrent hysteresis are obtained. Abstract : The structural advantages and localized surface plasmon resonance effect of Ag@SiO2 nanowires are utilized to improve light harvesting, accelerate electron transmission, promote electron–hole separation, and suppress charge‐carrier recombination. By optimizing the concentration of Ag@SiO2 nanowires, a high power conversion efficiency (18.03%) and a negligible photocurrent hysteresis are achieved.